Bike Sharing Operation: Case Study in Bandaraya Johor Bahru - Fathin Roslan, Nuur; Khatijah Hassan, Siti; Nordin, Latifah; Zaly, Muhammad; Suraini, Mimi; Nazar, Lutfi; Ramzi, Mohd (International Journal of Engineering and Technology, 2018)
Bike-sharing is a system that allows people to rent bicycle at one of automatic rental stations scattered around the city, use them for a short journey and return them at any station in the city. A crucial factor for the success of a bike sharing system is its ability to meet the ï¬‚uctuating demand for bicycles and for vacant lockers at each station. The main goal when implement bike sharing (BS) is to introduce non-motorized vehicles that can substitute other public transport with more positive impact towards the transportation systems. The objectives of this paper are to identify the facility for bike sharing operation in Bandaraya Johor Bahru and to promote Bike Sharing to citizen of Johor.Â Â